Making the American Mouth : Dentists and Public Health in the Twentieth Century. - Picard, Alyssa (Critical issues in health and medicine., 2009)
Why are Americans so uniquely obsessed with teeth? Perfect white, straight teeth. Making the American Mouth is at once a history of U.S. dentistry and a study of a billion-dollar industry. Alyssa Picard chronicles the forces that limited Americans' access to dental care in the early twentieth century and addresses the ways dentists worked to expand that accessand improve the public image of their profession. Comprehensive in scope, Making the American Mouth describes how dentists' early public health commitments withered under the strain of fights over fluoride, midcentury social movements fo.